2013
DOI: 10.1103/physreve.88.032803
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary vaccination dilemma in complex networks

Abstract: In this work we analyze the evolution of voluntary vaccination in networked populations by entangling the spreading dynamics of an influenza-like disease with an evolutionary framework taking place at the end of each influenza season so that individuals take or not the vaccine upon their previous experience. Our framework thus put in competition two well-known dynamical properties of scale-free networks: the fast propagation of diseases and the promotion of cooperative behaviors. Our results show that when vac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 48 publications
(56 reference statements)
1
54
0
Order By: Relevance
“…However, if the vaccine is imperfect, a crossover effect occurs such that the ER graphs are more effective than SF networks in enhancing vaccination. In [526], these results are mainly attributed to the competition of two processes taking place. One is the propagation of the diseases, and second is the uptake of vaccination behavior.…”
Section: Impact Of Interaction Network Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the vaccine is imperfect, a crossover effect occurs such that the ER graphs are more effective than SF networks in enhancing vaccination. In [526], these results are mainly attributed to the competition of two processes taking place. One is the propagation of the diseases, and second is the uptake of vaccination behavior.…”
Section: Impact Of Interaction Network Topologymentioning
confidence: 99%
“…Despite of the inspiring progress, there does not exist a direct comparison between a perfect and an imperfect vaccine in [525]. Aiming to clarify this, Cardillo et al introduced a tunable parameter τ to modulate the quality of the vaccine in influenza-type disease, the vaccine being perfect at τ = 0 and useless at τ = 1 [526]. When the vaccine is perfect, the research revealed that SF networks outperform ER graphs, since the overall vaccinated (infected) number is larger (smaller) on SF networks.…”
Section: Impact Of Interaction Network Topologymentioning
confidence: 99%
“…Such human behavioral responses can have significant effects on the epidemic dynamics, 1-5 a topic of great recent interest. [6][7][8][9][10][11][12][13][14] The individual reactions to an epidemic often rely on detailed information about the disease. Broadly, there are two types of information: local or global.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it has been argued that efficient immunization strategies can be developed by considering the higher-order organization of connectivity patterns [57,69,70,71,72,73,74]. Further studies proposed vaccination strategies using evolutionary games [75], or considering complex contagion processes [76]. For a recent review on the subject we refer the readers to Ref.…”
Section: Introductionmentioning
confidence: 99%